Outcomes and nursing workload related to obese patients in the intensive care unit. (August 2016) - Carrara, Fernanda Souza Angotti; Zanei, Suely Sueko Viski; Cremasco, Mariana Fernandes; Whitaker, Iveth Yamaguchi
Summary: Objectives: To compare the morbidity and mortality of patients with a body mass index (BMI) < and ≥30 kg/m 2 and to identify risk factors related to death and length of stay of obese patients in the intensive care unit (ICU). Methods: Prospective and cross-sectional study. Setting: A 35-bed mixed ICU in São Paulo, Brazil. Results: The sample consisted of 530 patients, of which 105 (19.8%) had a BMI ≥30 kg/m 2 . A significantly higher number of obese patients were female ( p = 0.025). The mortality, morbidity and nursing workload were not different between the obese and nonobese groups. However, the morbidly obese patients were younger ( p < 0.001), had a lower Charlson Comorbidity Index (CI; p = 0.002), lower Simplified Acute Physiology Score 3 (SAPS 3; p = 0.047), lower Sepsis-related Organ Failure Assessment (SOFA) score ( p = 0.019), shorter ICU length of stay (LOS; p = 0.015) and hospital LOS ( p = 0.039), and an increased mean nursing workload (Nursing Activities Score (NAS; p = 0.004)). The SOFA score and nursing workload were identified as risk factors associated with death in the ICU. These two variables, in addition to the admission category and duration of mechanical ventilation (MV), were also related to the ICU LOS, which demonstrates an inverse relationship between the NAS and LOS. Conclusion: Although the morbidity, mortality and nursing workload were not significantly different between the obese and nonobese groups, our results contribute additional information to the relationship between obesity and clinical discharge and inform future research.